PENDIDIKAN ANAK BINA KELUARGA REMAJA (BKR) DI KAMPUNG KB TANAH OMBAK KELURAHAN PURUS KECAMATAN PADANG BARAT KOTA PADANG - Riri Lestari; Alexander Syam (JURNAL MANAJEMEN PENDIDIKAN, 2020)
BKR policy is to form and develop BKR, improve BKR quality, increase commitment with stakeholders and partners in BKR management, improve BKR services that are integrated with PIK RM activities and provision and improvement of HR competencies. Meanwhile, the strategy taken is to carry out advocacy on the growth and development of BKR, promote and socialize BKR, provide budget support for BKR's work both from APBN, APBD funds and from other funding sources, carry out training and orientation for HR BKR managers and develop substance materials. BKR is in accordance with the needs of teenage families. The operational strategies for BKR are: (1) BKR groups synergize with PIK KRR, (2) so that parents encourage their teenagers to participate in PIK KRR activities, (3) Form as many BKRs as possible so that each village can make a pilot. The establishment of BKR in the Kampung KB Tanah Ombak village was commemorated by the formation of the KB Village in 2015, in Kampung KB Tanah Ombak had 1 reading garden Tanah Ombak which existed before the formation of Kampung KB. Manager of Youth Family Development (BKR) Tanah Ombak activities.